IDENTIFIKASI PENGGUNAAN BAHAN AJAR PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 1 TAMAN - RIEKE INDRIATI (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Teaching materials represent important study appliance in course of learning to teach specially to a educator. But in reality still many used teaching materials a educator without considering feasibility the standard of National Education Standards Agency (BSNP). This study aims to determine what teaching materials are used and the reasons teachers using it, the feasibility of the teaching materials used assessed the feasibility of the component based on the content, presentation, language, and graph to teaching materials used in teaching accounting SMAN 1 Taman. Tecniques of data collection using interview and documentation. The results of this study indicate that use teaching materials are text books and worksheets. Feasibility of text book is 87,02% or included in the criteria is very feasible, while the feasibility of teaching materials worksheets is 80,94% or included in the criteria very feasible. Keywords : teaching materials, feasibility